Optic disc drusen presenting as papilledema: a case report - Sitaula, S; Thapa, M; Sharma, AK (Journal of Chitwan Medical College, 2014)
Optic disc drusens, which are congenital anomalies of optic nerve head, are depositions of mucopolysaccharides and proteinaceous material within the optic nerve head. They are usually bilateral and diagnosed incidentally during routine fundus examination where they may be mistaken for papilledema. We report a case of 63 year old female referred to the neuro-ophthalmology department with the clinical suspicion of disc edema. Simple noninvasive investigations like ultrasound B-scan, fundus autofluorescene along with the newer test like spectral domain optical coherence tomography helped us to diagnose it as a case of pseudopapilledema, as optic disc drusen. Thus, a high index of suspicion along with the ancillary tests is helpful in differentiating optic disc drusen from true papilledema. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10848 Journal of Chitwan Medical College 2014; 4(1): 42-44